Effects Of Cable Diameter Reduction And Snapping On The Behavior Of Cable-Stayed Bridges - Ajaj, Sayed Mahamed (2007)
Cable–stayed bridges are usually constructed in coastal area in which the surrounding atmospheric is considered as severe environmental condition. This atmosphere helps in building up quickly the corrosion of steel cables with time. Visual inspection of cable-stayed bridges built up worldwide shows that the bridge cables suffer from serious corrosion although the cables are protected using different techniques. There is a considerable reduction in cable diameter due to corrosion, which depends on the severity of the environmental condition. There is no sufficient information regarding the effect of reduction in cable diameter on the structural response of cable-stayed bridge. Furthermore, snapping of cables due to accidental and /or corrosion is another important issue which affecting the structural response and safety of cable stayed bridges and need to be addressed for safe design.In this research, the effect of reducing cables diameter, cables layout and snapping of individual cables on the structural behavior and safety of cable-stayed bridge are presented. Three cable layouts are analyzed in this study i.e. harp, semi harp and fan layouts. In each layout, five different reductions in cables diameters are considered i.e 12.50%, 25.00%, 37.50%, and 50.00%. To address snapping of cable, harp bridge layout is considered and the structural behavior of the bridge due to snapping individual cables in the bridge are presented and discussed. The analysis starts with initial shape analysis to stress the cables to minimize the deformation under self-weight of the structure. The analysis was carried out using stiffness method considering the geometrical nonlinearities. The results of initial shape analysis show that in all bridge layouts reflect comparable behavior. The cable forces were found to be the lowest in fan layout cable bridge compared to harp and semi harp layouts. Reducing cables diameter will lead to a redistribution of forces and moment in different components of the bridge and alter the structural behavior in a nonlinear fashion. Reducing cables diameter by 25% will compromise the bridge safety as the stresses in cables, deformation, and bending moment will be increased significantly. The bridge cable layouts have little effect on the structure response of the cable-stayed bridge with reduced cables diameter. The fan layout shows better structural response compared to harp and semi harp layout, especially in term of cable forces and deformation profile. Notwithstanding this fact, 25% of cables reduction diameter will significantly affect the moment in girder of fan bridge layout compared to other layouts of cables Snapping the individual cable in the bridge has a significant effect on the cable force and bending moment distribution in the girder, tower and will cause bridge failure.